Effectiveness of Lumbar Corset Use in Reducing Primary Dysmenorrhea Pain among Adolescent Girls - Ni Made Dea Maretha; Ni Rai Sintya Agustini; Yohanes Zenriano Tarigan (Discover Health and Medicine, 2026)
Introduction: Primary dysmenorrhea is a common complaint among adolescent girls and can significantly interfere with daily activities and academic performance. One non-pharmacological intervention that may help alleviate dysmenorrhea pain is the use of a lumbar corset, which provides postural support and reduces muscle tension in the lower back region. Methods: This study employed a pre-experimental design using a one-group pretest–posttest approach. The study population consisted of female students at SMP Negeri 2 Melaya who experienced primary dysmenorrhea. A total of 47 participants were selected using convenience sampling. The intervention involved wearing a lumbar corset for 2 hours per day during menstruation. Pain intensity was measured before and after the intervention using the Visual Analog Scale (VAS). Data were analyzed using the Wilcoxon Signed Rank Test. Results: Prior to the intervention, most participants reported moderate to severe pain levels. Following the use of the lumbar corset, a significant reduction in pain intensity was observed. The Wilcoxon test showed a Z value of −6.283 with p < 0.001, indicating a statistically significant difference between pain scores before and after the intervention. Conclusion: The findings indicate that lumbar corset use is effective in reducing primary dysmenorrhea pain among adolescent girls. Further studies employing a control group and larger sample sizes are recommended to strengthen the evidence and generalizability of the results.